Memetakan Cakrawala Intelektual: Menggali Teori Ushul Fikih Yudian Wahyudi dan Wahbah Zuhaili - Afthon Yazid; Sugitanata, Arif; Siti Aminah (STAINI Press, 2024)
This article explores the significant contributions of two Muslim scholars, Yudian Wahyudi from Indonesia and Wahbah Zuhaili from Syria, in the development of Ushul Fikih, which is a methodology in Islamic law. This research is qualitative literature research. Where researchers look at previous literature through journals and books related to both figures. The article also describes how Ushul Fikih in Indonesia has evolved along with the social, religious, and political dynamics of the country, becoming an important tool for Muslim scholars and scholars to integrate Islamic principles with local values. The works of Wahyudi and Zuhaili complement each other, with Wahyudi focusing on the contextualization of Islamic law and Zuhaili on dynamic and adaptive ijtihad. The results of this research explain that the two figures sought to bridge the gap between tradition and modernity and between universal Islamic principles and specific local applications. Ushul Fiqh has been an important instrument in ensuring that Islamic law remains relevant and beneficial to society.